Pensamientos irracionales y su influencia en las relaciones intrafamiliares de un adolescente de 16 años - Delgado Cruz, Meylin Liliana (2020)
The present research aims to determine the influence of irrational thoughts in the intra-family relationships of a 16-year-old adolescent. To carry out this research, techniques such as: the interview, clinical observation, semi-structured interview and instruments such as the Beck depression questionnaire and the Hamilton anxiety scale were used, which were not applied to make a diagnosis but rather to rule out these disorders, with a rational emotional therapeutic approach. In the same way, how the family relationship is affected by irrational thoughts causing discomfort in their family dynamics; this research shows the importance of identifying irrational thoughts and thus can prevent emotional distress and our behavior in certain situations.